Material Based Penalty-Cost Quantification Model for Construction Projects Influencing Waste Management - Nawaz, Ahsan; Chen, Jian; Su, Xing; Zahid Hassan, Hafiz Muhammad (Frontiers in Environmental Science, 2022)
The Construction and demolition (C and D) waste generation is a critical issue for the construction industry, which negatively affects the economy, environment, and society. This study estimates the penalty-cost based on the produced C&D wastes in steel and concrete skeleton projects. Field survey and the BOQ data were collected from five concrete and four steel skeleton projects. The difference of materials used and wastes generated between concrete and steel skeleton projects were evaluated statistically (ANOVA and Welch and Brown-Forsythe). A financial analysis was implemented for estimating the penalty cost. The study outcomes demonstrate that the amount of waste that construction managers estimated is significantly lower than the actual amount generated. Furthermore, 0.055% of the total project cost of a penalty was estimated based on the waste produced at construction sites. In the end, the estimated penalty was validated by comparing it with the six recent completed projects. The penalty calculated in this study could save the project cost and reduce the C&D waste. As a result, imposing the estimated cost as a penalty would force construction managers to think thoroughly about the generated C&D waste problems. This study also has a novelty and will add to the body of knowledge by using penalty-cost quantification model to save project-cost of construction material-based-waste, and it can be further explored by adopting more quality data and engaging different construction materials.